OCULAR MANIFESTATIONS OF SHAKEN BABY SYNDROM - Tatyana V. Kukuyuk; Elena V. Gromakina; Galina G. Basova (Фундаментальная и клиническая медицина, 2016)
Here we present two clinical cases of shaken baby syndrome (SBS) ocular manifestations. SBS, being life-threatening condition, is important for providing an adequate treatment for violated children. An information about SBS can assist parents in avoiding traumas